'Ruined and Lost': Spanish Destruction of the Pearl Coast in the Early Sixteenth Century. (1st May 2009) - Perri, Michael
Abstract : In the early sixteenth century, the area that today comprises eastern Venezuela and its offshore islands enriched Spain with pearls, supplied Spanish colonists with Indian slaves, and generated high hopes of finding interior civilisations rich in gold. However, the prosperity of Spanish colonies in this region (called the Pearl Coast) proved tragically short-lived, lasting less than two decades. Using Garrett Hardin's concept of the 'tragedy of the commons', this article examines Spanish overexploitation of both the oyster beds around the island of Cubagua and the native peoples along the mainland by competing groups of Spaniards. Building upon the works of historians such as Pablo Ojer and Enrique Otte, and utilising archival research and Otte's seldom-used compilations of primary documents, this article analyses the dramatic but little-known history of the Pearl Coast, where damage to the environment went hand in hand with the enslavement and decimation of native populations.